Do accessory parameters affect the outcome of the endoscopic procedures in female infertile patients?: an experience at a single tertiary care center - Agrawal, Namita; Yadav, Poonam; Fayyaz, S.; Jain, Tarun Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In modern era, endoscopic methods are commonly used in evaluation of female infertility. Hysterolaparoscopy is such a real time theranostic modality for anatomical causes of the infertility. The objective of this study was to evaluate the effect of accessory parameters (Age, Body mass index, duration of infertility, Rhesus factor, menstruation history and hemoglobin) on success rate of endoscopic procedures in terms of achieving pregnancy. Methods: A total 157 female infertile patients (Mean± standard deviation 27.72±3.82 years) were recruited in present study. During initial assessment detailed history was taken and hysterolaparoscopy was performed. The observed structural abnormalities on hysterolaparoscopy during diagnostic work up were tackled at same time if possible. After procedure, patients were counselled for regular sexual activity. The follow-up of all patients was done for 12 months. Results: A total 157 female infertile patients were recruited and divided into primary 93 (59.2%) and secondary infertile 64 (41.74%) patients on basis of obstetric history. The average age, BMI, hemoglobin and duration of infertility were 27.7years, 21.8 kg/m2, 12.3 gm and 3.9 years respectively. Out of 157 patients, anatomical abnormalities were detected in 125 patients during Hysterolaparoscopy and distributed in 77/93 (82.8%) primary and 48/64 (75%) secondary infertile patients. Of 125 patients with abnormal hysterolaparoscopic findings, 121 underwent active intervention and on follow up, 43 patients were conceived. We found that age; BMI, Rhesus factor, menstruation history and duration of the infertility were not correlated with fertility outcome while hemoglobin level was significantly correlated with conception rate. Conclusions: Authors concluded that outcome of the hysterolaparoscopy in female infertile patients is significantly depends upon hemoglobin levels, however outcome is irrelevant to age, duration of infertility, Rhesus factor and body mass index.